Nonlinear optical properties of Sn(IV) phthalocyanines: experimental and theoretical approach - Louzada, Marcel Severiano (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
This work presents the nonlinear properties of six Sn(IV) Phthalocyanines. Three of the phthalocyanines are linked by an alkylthiol substituent and the rest are linked with a phenoxy substituent. For all six compounds non-linear optic analysis was carried out in four solvents: chloroform, toluene, dichloromethane, and tetrahydrofuran, and their differences were recorded. Calculation of the linear, singlet excited, triplet excited and two photon absorption cross-sections were also carried out and the results compared. To form a comparison the first order hyperpolarizabilities, DFT calculations were also performed and the results compared to see if the behaviour between the two properties can be predicted using DFT.
Keywords: Phthalocyanines; Nonlinear optics